FROM BURMEISTER TO AMEGHINO AND THE WORLDWIDE RECOGNITION OF THE VERTEBRATE PALEONTOLOGY FROM ARGENTINA - Mariano Bond (Publicación Electrónica de la Asociación Paleontológica Argentina, 2025)
Francisco J. Muñiz was undoubtedly the first national Argentine paleontologist, preceding Florentino Ameghino with its pioneering descriptions of the fossil bearing beds in Luján and their fossil mammals, including “Muñi-felis”. In 1861, the German naturalist Hermann Burmeister (G. Burmeister, here after) arrived in Argentina to become the Museo Público de Buenos Aires Director. G. Burmeister renovated the institution and founded the Anales del Museo, one of the oldest Argentine scientific publications. In his last years, the Museo de La Plata was consolidated under the leadership of Francisco Pascasio Moreno, who was the creator and served as its Director from 1884 to 1906. Under the direction of Moreno, the museum attracted eminent researchers, including F. Ameghino and his brother Carlos. When the Ameghino brothers left the institution, figures such as Alcides Mercerat and Santiago Roth replaced them. Roth became a key rival to Carlos in exploring Patagonian deposits with vertebrate fossils. F. Ameghino brought global visibility and reconnaissance of the Argentine paleontology due to his numerous publications based on the collections largely made by his brother Carlos and his appointment as the Director of the Museo Nacional de Buenos Aires in 1902. After the death of Florentino, Carlos remained active at this museum, where a new generation of paleontologists emerged. Among them, Lucas Kraglievich stayed briefly in the Museo de La Plata after the death of Roth. Then the Spanish mastozoologist Ángel Cabrera assumed as the Head of Paleontology, marking a notable stage in the Paleontology of Argentina.